ANTARA MIHRAB, ISTANA, DAN PADANG PASIR : RETORIKA DAN ESTETIKA SASTRA ARAB MASA DINASTI UMAYYAH - Muh. Japri; Muhsin Muhsin; Haniah Haniah (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2026)
This study aims to deeply analyze the development, aesthetic characteristics, and rhetorical dimensions of prose and poetry during the Umayyad Dynasty in close integration with the socio-political dynamics of the era. The method employed is descriptive-analytical qualitative with a historical-sociological approach to examine classical Arabic literary texts and secondary documents. The results indicate that Umayyad literature transformed massively through the emergence of political poetry (syi'ir al-siyasi), polemical poetry (al-naqoid), and love poetry (syi'ir al-ghazal), alongside rapid advancements in prose forms such as sermons, correspondence (rasail), and official administration (kitabah). This dynamic was fueled by the polarization of major cultural regions (Hijaz, Iraq, and Syria), each giving birth to its own distinct rhetorical and aesthetic styles. This aesthetic shift occurred because state stabilization, royal financial support, and the rise of religious-political factions necessitated rhetorical instruments for propaganda and ideological hegemony to sway the masses. The study concludes that Umayyad literature was not merely an individual artistic expression but a structured instrument of political power that reconstructed the Arabic language toward systemic modernization. Consequently, this study contributes to the theoretical understanding of the dialectic between political authority and linguistic aesthetics in Islamic civilization.